The Effects of Audio-Visual Aids on Teaching Civilization Course within EFL Classes Case study :Third Year LMD Students –Laghouat University - KABACHE ,Ameur; BAKHOUCHE, Salah (Faculty of Letters and Foreign Languages Department of English, 2018)
This research aims at highlighting a hypothesized correlation between two variables: an independent variable which is the audio visual aids and a dependent variable which is the teaching-learning of the civilization course within EFL classes. The nature of the research is descriptive. The research’s main gathering data tool is the questionnaire which was delivered into two samples; one is addressed to teachers and the other to students at the University of Laghouat. Once we gathered the necessary findings, the analysis and interpretation attempted to demonstrate and prove the existence of a certain effect of Audio-Visual Aids on teaching learning civilization course within EFL classes